PERENCANAAN TEBAL PERKERASAN KAKU DI RUAS JALAN TAMAN RAHAYU PADA PROYEK PEMBANGUNAN JALAN TOL CIMANGGIS – CIBITUNG SEKSI 2 KOTA BEKASI - Doni Haidar Nur (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2019)
Rigid Pavement is a type of road pavement that uses concrete as the main material for pavement, is one type of road pavement that is used apart from flexible pavement. Pavement is generally used on roads that have fairly congested traffic conditions and have a large load distribution, such as on inter-provincial roads, toll roads, and at signal intersections. Rigid pavement (Rigid pavement) is used because the implementation is relatively simple except for connections with a planned life can reach 15-40 years lower maintenance costs compared to asphalous pavement.This study aims to calculate the CBR value and calculate the thickness of rigid pavement in Taman Rahayu Road Section.The method used in this research is a case study in the Section 2 Cimanggis-Cibitung Toll Road Development Project by collecting CBR data and traffic data.The results of this study for the planning of road pavement thickness with a planned age of 20 years were 30 cm concrete plates, 10 cm Lean Concrete and 15 cm Aggregate drainage layers.